A preparation method of battery cathode material and cathode material and application thereof
Through parallel spinning technology and high-temperature calcining process, a dual-function FeNi single-atom catalyst was prepared, which solved the problems of uneven distribution of dual-function catalysts and active site coverage in the prior art, and significantly improved the electrochemical performance of rechargeable zinc air batteries.
Patent Information
- Application Number
- CN202510052633.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
It is difficult to effectively prepare dual-function oxygen reduction (ORR) and oxygen precipitation (OER) catalysts for rechargeable zinc air battery cathode materials, resulting in slow reaction kinetics during charging and discharging, large voltage gaps and poor energy efficiency during charging and discharging.
The dual-function FeNi single-atom catalyst is prepared by parallel spinning technology combined with high-temperature calcining technology. This method uses electrospinning technology to spin Fe-ZIF-8 and Ni-ZIF-8 seeds into nanofibers and calcined at high temperature to form a bifunctional catalyst based on carbon fibers.
The uniform distribution and high catalytic activity of the dual-function catalyst are achieved, the coverage of active sites is reduced, and the open circuit voltage and peak power density of zinc air batteries are improved, which is better than the catalysts prepared by traditional physical mixing methods.
Smart Images

Figure CN119481101B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a method for preparing and applying a battery cathode material. Background Technology
[0002] With the increasing severity of the global energy crisis and environmental pollution, the development of clean and efficient energy storage and conversion devices has become particularly urgent. Zinc-air batteries, with their inherent safety, environmental friendliness, and high theoretical energy density (1086 Wh / kg), stand out among many energy storage systems, powering numerous emerging applications. However, for rechargeable zinc-air batteries, the cathode reaction kinetics during discharge and charging are very slow, resulting in a large voltage difference between charge and discharge and poor energy efficiency. Therefore, there is an urgent need to prepare bifunctional catalysts for oxygen reduction (ORR) and oxygen evolution (OER) that simultaneously meet the requirements of the charge and discharge processes for use as cathode materials in zinc-air batteries.
[0003] Achieving dual functionality from a single material is challenging. Although noble metal electrocatalysts (such as Pt and Ru) are widely used in the preparation of zinc-air battery cathode materials, they suffer from high cost and limited functionality. Currently, the main technical method for preparing bifunctional battery cathode catalytic materials involves physically mixing catalysts with ORR and OER active components, respectively. This method suffers from poor compatibility, difficulty in controlling the uniform distribution of the catalyst, and a tendency to cover active sites, hindering further improvements in zinc-air battery performance. Therefore, designing effective bifunctional electrocatalysts for air cathodes is crucial for accelerating the commercialization of rechargeable zinc-air batteries. Summary of the Invention
[0004] The purpose of this section is to outline some aspects of the embodiments of the present invention and to briefly describe some preferred embodiments.
[0005] The first aspect of the present invention provides a method for preparing a battery cathode material:
[0006] First, Fe-ZIF-8 seed crystals and Ni-ZIF-8 seed crystals are prepared into spinning solutions and then placed in two spinning needles arranged in parallel for electrospinning. After that, they are calcined at a high temperature of 950~1000 °C to obtain catalysts. The catalysts are then used to make catalyst slurry and drop-coated onto carbon cloth to obtain battery cathode materials.
[0007] As a preferred embodiment of the preparation method described in this invention, the preparation method of the catalyst slurry includes: mixing the catalyst, ethanol, and Nafion solution to obtain the catalyst slurry.
[0008] As a preferred embodiment of the preparation method described in this invention, the applied voltage is 18~22 kV, the spinning rate is 1~1.2 mL / h, and the receiving distance is 12~15 cm.
[0009] As a preferred embodiment of the preparation method described in this invention, the catalyst preparation method comprises the following steps:
[0010] Step 1: Mix zinc salt, iron salt and organic ligand and add to solvent to prepare Fe-ZIF-8 seed crystals; mix zinc salt, nickel salt and organic ligand and add to solvent to prepare Ni-ZIF-8 seed crystals;
[0011] Step 2: Mix the Fe-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution A; mix the Ni-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution B;
[0012] Step 3: Place spinning solution A and spinning solution B into two spinning needle tubes respectively, and use the spinning needles arranged in parallel to perform electrospinning to obtain FeNi bimetallic nanofibers.
[0013] Step 4: The FeNi bimetallic nanofibers prepared in Step 3 are pre-oxidized, then calcined at 950~1000 °C, and naturally cooled to obtain the catalyst.
[0014] As a preferred embodiment of the preparation method described in this invention: in step 1, the zinc salt is zinc nitrate hexahydrate; the iron salt is ferric nitrate nonahydrate; and the nickel salt is nickel nitrate hexahydrate.
[0015] As a preferred embodiment of the preparation method described in this invention: in step 2, the polymer is polyacrylonitrile and polyvinylpyrrolidone; the spinning solvent is N,N-dimethylformamide; the mass ratio of the Fe-ZIF-8 seed crystal, polymer, and spinning solvent is 5~7:3:35~40; the mass ratio of the Ni-ZIF-8 seed crystal, polymer, and spinning solvent is 5~7:3:35~40.
[0016] As a preferred embodiment of the preparation method described in this invention: in step 1, the mass ratio of zinc salt, iron salt and organic ligand is 28~35:1:33~40; the mass ratio of zinc salt, nickel salt and organic ligand is 2~3:2:9~11; the organic ligand includes dimethylimidazole; the solvent includes methanol.
[0017] As a preferred embodiment of the preparation method described in this invention: in step 4, the pre-oxidation heating rate is 1~2℃ / min, in an air atmosphere, and the pre-oxidation time is 2~3 h; the high-temperature calcination heating rate is 5~6℃ / min, in a nitrogen atmosphere, and the calcination time is 2~3 h.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] (1) This invention uses parallel spinning technology combined with high-temperature calcination to prepare a bifunctional FeNi single-atom catalyst. This preparation method avoids the problem of coverage between different catalytic reaction active sites caused by traditional physical mixing methods. In addition, the parallel spinning technology realizes the interaction between the two catalytic active sites, ensuring that the two active sites are fully exposed and uniformly distributed. Moreover, the preparation process is simple, the material cost is low, and large-scale production can be realized.
[0020] (2) The bifunctional FeNi single-atom catalyst material obtained by parallel spinning technology provided by the present invention has high catalytic activity. The carbon nanofibers provide a network structure with high conductivity, which accelerates the electron transfer rate. The FeNi dual active sites ensure the bifunctional activity of the catalyst and exhibit a small ΔE (0.66 V).
[0021] (3) The bifunctional FeNi single-atom catalyst provided by this invention was used as an air cathode to assemble a rechargeable zinc-air battery, which exhibited a high open-circuit voltage (1.53 V) and a high peak power density (252 mW / cm²). 2 This method is superior to bifunctional catalysts prepared by simple physical mixing methods, providing a new approach for preparing air cathode materials for highly active bifunctional rechargeable zinc-air batteries. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below, wherein:
[0023] Figure 1 This is a photograph of the cathode electrode material used in the sample of Example 1 for a rechargeable zinc-air battery.
[0024] Figure 2 Here is a scanning electron microscope image of the sample from Example 1;
[0025] Figure 3 The X-ray diffraction pattern of the sample in Example 1;
[0026] Figure 4 The LSV test curves for samples from Examples 1-3 are shown below.
[0027] Figure 5 The open-circuit voltage curves are for the rechargeable zinc-air batteries assembled with air electrode materials for the samples of Examples 1 and 4.
[0028] Figure 6 The discharge curves and power density curves of the rechargeable zinc-air batteries assembled with air electrode materials for the samples of Examples 1, 4 and 5 are shown.
[0029] Figure 7The constant current discharge curves of the rechargeable zinc-air battery assembled with air electrode material in Example 1 are shown at different current densities.
[0030] Figure 8 The rechargeable zinc-air battery used in the assembly of air electrode materials for Example 1 was tested at 10 mA cm⁻¹. -2 The constant current charge-discharge curves at the current density. Detailed Implementation
[0031] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.
[0032] Example 1:
[0033] This embodiment provides a bifunctional FeNi single-atom catalyst obtained by parallel spinning technology, and the preparation method is as follows:
[0034] (1) 3.94 g dimethylimidazole, 3.36 g zinc nitrate hexahydrate and 120 mg ferric nitrate nonahydrate were added to 600 mL methanol, stirred for 12 h and washed four times with deionized water, and dried to obtain Fe-ZIF-8 seed crystals; 10.59 g dimethylimidazole, 2.37 g zinc nitrate hexahydrate and 2.34 g nickel nitrate hexahydrate were added to 600 mL methanol, stirred for 12 h and washed four times with deionized water, and dried to obtain Ni-ZIF-8 seed crystals.
[0035] (2) Take 0.35 g Fe-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone (Aladdin, P110607) and 0.14 g polyacrylonitrile (Aladdin, P303197) and dissolve them in 2.45 g N,N-dimethylformamide solvent to obtain spinning solution A; take 0.35 g Ni-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone and 0.14 g polyacrylonitrile and dissolve them in 2.45 g N,N-dimethylformamide solvent to obtain spinning solution B. Spinning solutions A and B were placed in two separate spinning needles. Two spinning needles, arranged side-by-side and close to each other, with an inner diameter of 0.62 mm and an outer diameter of 0.9 mm, were used for electrospinning under a high-voltage electric field of 18 kV. Both spinning solutions A and B were 2.5 mL each. The distance between the spinning needles and the receiving roller was 12 cm. The spinning rate was 1 mL / L at room temperature, yielding FeNi bimetallic nanofibers with a thickness of approximately 5 µm. These nanofibers were then subjected to pre-oxidation in air at a heating rate of 1 °C / min to 280 °C, held for 2 h, and allowed to cool naturally. They were then calcined again at a heating rate of 5 °C / min to 1000 °C, held for 2 h, and allowed to cool naturally to room temperature. Finally, a bifunctional FeNi single-atom catalyst based on a carbon fiber substrate was obtained. (Image of the catalyst is shown below.) Figure 1 As shown.
[0036] Example 2:
[0037] This embodiment provides a Fe single-atom catalyst obtained by parallel spinning technology, and the preparation method is as follows:
[0038] (1) 3.94 g of dimethylimidazole, 3.36 g of zinc nitrate hexahydrate and 120 mg of ferric nitrate nonahydrate were added to 600 mL of methanol, stirred for 12 h, washed four times with deionized water, and dried to obtain Fe-ZIF-8 seed crystals.
[0039] (2) Take 0.35 g Fe-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone and 0.14 g polyacrylonitrile and dissolve them in 2.45 g N,N-dimethylformamide solvent to obtain spinning solution A; divide 5 mL of spinning solution A into two equal parts and place them in two spinning needle tubes respectively. Use two spinning needles arranged in parallel. The specifications of the two spinning needles are 0.62 mm inner diameter and 0.9 mm outer diameter. Electrospinning is carried out under a high voltage electric field of 18 kV. The distance between the spinning needle and the receiving roller is 12 cm. The spinning rate is 1 mL / L. At room temperature, Fe metal nanofibers with a thickness of about 5 µm are obtained. The catalyst was then placed in air and heated to 280 °C at a rate of 1 °C / min for pre-oxidation. After holding for 2 h, it was allowed to cool naturally and then heated to 1000 °C at a rate of 5 °C / min for secondary calcination. After holding for 2 h, it was allowed to cool naturally to room temperature, thus obtaining a single-atom Fe catalyst based on carbon fiber.
[0040] Example 3:
[0041] This embodiment provides a Ni single-atom catalyst obtained by parallel spinning technology, and the preparation method is as follows:
[0042] (1) 10.59 g of dimethylimidazole, 2.37 g of zinc nitrate hexahydrate and 2.34 g of nickel nitrate hexahydrate were added to 600 mL of methanol, stirred for 12 h, washed four times with deionized water, and dried to obtain Ni-ZIF-8 seed crystals.
[0043] (2) Take 0.35 g Ni-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone and 0.14 g polyacrylonitrile and dissolve them in 2.45 g N,N-dimethylformamide solvent to obtain spinning solution B. Divide 5 mL of spinning solution B into two equal parts and place them in two spinning needle tubes respectively. Use two spinning needles arranged side by side. The specifications of the two spinning needles are 0.62 mm inner diameter and 0.9 mm outer diameter. Electrospinning is carried out under a high voltage electric field of 18 kV. The distance between the spinning needle and the receiving roller is 12 cm. The spinning rate is 1 mL / L. At room temperature, Ni metal-containing nanofibers with a thickness of about 5 µm are obtained. The catalyst was then placed in air and heated to 280 °C at a rate of 1 °C / min for pre-oxidation. After holding for 2 h, it was allowed to cool naturally and then heated to 1000 °C at a rate of 5 °C / min for secondary calcination. After holding for 2 h, it was allowed to cool naturally to room temperature, thus obtaining a Ni single-atom catalyst based on carbon fiber.
[0044] Example 4:
[0045] This embodiment provides a FeNi single-atom catalyst obtained by classical electrospinning technology. The preparation method is as follows:
[0046] (1) 3.94 g dimethylimidazole, 3.36 g zinc nitrate hexahydrate and 120 mg ferric nitrate nonahydrate were added to 600 mL methanol, stirred for 12 h and washed four times with deionized water, and dried to obtain Fe-ZIF-8 seed crystals; 10.59 g dimethylimidazole, 2.37 g zinc nitrate hexahydrate and 2.34 g nickel nitrate hexahydrate were added to 600 mL methanol, stirred for 12 h and washed four times with deionized water, and dried to obtain Ni-ZIF-8 seed crystals.
[0047] (2) Take 0.35 g Fe-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone, and 0.14 g polyacrylonitrile and dissolve them in 2.45 g N,N-dimethylformamide solvent to obtain spinning solution A; take 0.35 g Ni-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone, and 0.14 g polyacrylonitrile and dissolve them in 2.45 g N,N-dimethylformamide solvent to obtain spinning solution B. Mix 2.5 mL of spinning solution A and 2.5 mL of spinning solution B and place them in a spinning needle tube. The spinning needle tube has an inner diameter of 0.62 mm and an outer diameter of 0.9 mm. Electrospinning is performed under a high voltage electric field of 18 kV. The distance between the spinning needle and the receiving roller is 12 cm. The spinning rate is 1 mL / L. The spinning environment is room temperature. FeNi bimetallic nanofibers with a thickness of about 5 µm are obtained. The catalyst was then placed in air and heated to 280 °C at a rate of 1 °C / min for pre-oxidation. After holding for 2 h, it was allowed to cool naturally and then heated to 1000 °C at a rate of 5 °C / min for secondary calcination. After holding for 2 h, it was allowed to cool naturally to room temperature, thus obtaining a single-atom FeNi catalyst based on carbon fiber.
[0048] Example 5:
[0049] This embodiment provides a bifunctional FeNi single-atom catalyst obtained by parallel spinning technology, and the preparation method is as follows:
[0050] (1) 4.8 g of dimethylimidazole, 4.2 g of zinc nitrate hexahydrate and 120 mg of ferric nitrate nonahydrate were added to 600 mL of methanol, stirred for 12 h, washed four times with deionized water, and dried to obtain Fe-ZIF-8 seed crystals; 12.87 g of dimethylimidazole, 3.5 g of zinc nitrate hexahydrate and 2.34 g of nickel nitrate hexahydrate were added to 600 mL of methanol, stirred for 12 h, washed four times with deionized water, and dried to obtain Ni-ZIF-8 seed crystals.
[0051] (2) Take 0.49 g Fe-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone (Aladdin, P110607) and 0.14 g polyacrylonitrile (Aladdin, P303197) and dissolve them in 2.8 g N,N-dimethylformamide solvent to obtain spinning solution A; take 0.49 g Ni-ZIF-8 seed crystals, 0.07 g polyvinylpyrrolidone and 0.14 g polyacrylonitrile and dissolve them in 2.8 g N,N-dimethylformamide solvent to obtain spinning solution B. Spinning solutions A and B were placed in two separate spinning needles. Two spinning needles, arranged side-by-side and close to each other, were used. Both needles had an inner diameter of 0.62 mm and an outer diameter of 0.9 mm. Electrospinning was performed under a 22 kV high-voltage electric field. The volume of both spinning solutions A and B was 2.5 mL. The distance between the spinning needles and the receiving roller was 15 cm. The spinning rate was 1.2 mL / L at room temperature, yielding FeNi bimetallic nanofibers with a thickness of approximately 5 µm. These nanofibers were then subjected to pre-oxidation in air at a heating rate of 2 °C / min to 280 °C, held for 3 h, and allowed to cool naturally. They were then calcined a second time at a heating rate of 6 °C / min to 950 °C, held for 3 h, and allowed to cool naturally to room temperature, ultimately yielding a bifunctional FeNi single-atom catalyst based on a carbon fiber substrate.
[0052] Characterization Example 1:
[0053] The bifunctional FeNi single-atom catalyst obtained in Example 1 was observed under a scanning electron microscope, and its morphology and structure are as follows. Figure 2 As shown.
[0054] from Figure 2 As can be seen, Example 1 successfully synthesized a catalyst with a continuously distributed nanofiber structure.
[0055] Characterization Example 2:
[0056] X-ray diffraction analysis was performed on the bifunctional FeNi single-atom catalyst obtained in Example 1, as follows: Figure 3 As shown.
[0057] Figure 3 Only two broad diffraction peaks were observed, confirming that the metal in the catalyst exists in single-atom form.
[0058] Test Example 1:
[0059] The electrochemical performance of the catalysts in Examples 1-3 was tested. The LSV scan rate was 5 mV / s, and the rotational speed of the rotating disk electrode was 1600 rpm.
[0060] The specific process is as follows:
[0061] Preparation of catalyst slurry: Take 2 mg of catalyst and place it in a centrifuge tube. Add 800 μL of ethanol and 5 μL of Nafion solution (perfluorosulfonic acid, Aladdin, N169478) and sonicate until a uniformly dispersed slurry is formed.
[0062] For ORR and OER tests, 5 μL of catalyst slurry was drop-coated onto the rotating disk electrode each time, for a total of 6 times, with a catalyst loading of 0.3 mg / cm³. 2 A calomel electrode was used as the reference electrode, and a platinum wire electrode was used as the counter electrode. A 1M potassium hydroxide solution was used as the electrolyte. Before testing, O2 was bubbled into the electrolyte for 1 hour to achieve O2 saturation. The ORR and OER performance of the catalyst were tested using a CHI660E electrochemical workstation.
[0063] The obtained data is as follows Figure 4 As shown, the catalyst of Example 1 exhibits an optimal ΔE of 0.66 V, demonstrating excellent bifunctional properties.
[0064] Example 6:
[0065] This embodiment provides a zinc-air battery, the preparation method of which is as follows:
[0066] Assemble a rechargeable zinc-air battery: The anode is a polished zinc sheet. According to the slurry preparation method described in Test Example 1, 400 μL of the catalyst slurry obtained in Examples 1, 4 and 5 are respectively drop-coated onto carbon cloth (Shengernuo Energy Mall, HCP330N, thickness of 0.33 mm) as the cathode. The electrolyte consists of 6 M potassium hydroxide and 0.2 M zinc acetate.
[0067] Battery performance was tested using a CHI 1140E electrochemical workstation at a scan rate of 5 mV / s.
[0068] The open-circuit voltage and power density of the assembled rechargeable zinc-air battery are as follows: Figure 5 and Figure 6 As shown, the rechargeable zinc-air battery assembled using the catalyst of Example 1 as an air cathode achieved an open-circuit voltage of 1.53 V and a peak power density of 252 mW / cm². 2 The performance was comparable to that of the zinc-air battery assembled in Example 5, but significantly superior to the zinc-air battery assembled with the mixed catalyst prepared in Example 4. This result is presumably because Example 4 directly mixed spinning solutions A and B, causing mutual masking between the active components, while the preparation methods of Examples 1 and 5 achieved full exposure of the bifunctional active sites. The carbon nanofibers ensured the uniform distribution of the active sites, and their excellent conductivity promoted electron transfer. Figure 7As shown, the rechargeable zinc-air battery assembled using the catalyst of Example 1 as the air cathode exhibits excellent stability at different current densities. Furthermore, the battery has a long lifespan at 10 mA cm⁻¹. -2 Under constant current charge-discharge testing at a current density, it can operate stably for 1400 hours. Figure 8 ).
[0069] In summary, this invention avoids the problem of overlapping active components caused by traditional physical mixing methods in the preparation of bifunctional catalysts. Furthermore, this invention achieves interaction between the dual catalytic active sites, ensuring sufficient exposure of the bifunctional active sites. Carbon nanofibers ensure the uniform distribution of active sites, and their excellent conductivity promotes electron transfer. This provides a novel method for cathode materials used in rechargeable zinc-air batteries.
[0070] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a battery cathode material, characterized in that: First, Fe-ZIF-8 seed crystals and Ni-ZIF-8 seed crystals are prepared into spinning solutions respectively, and then placed in two spinning needle tubes arranged in parallel for electrospinning, and then calcined at a high temperature of 950-1000°C to obtain a catalyst; the catalyst slurry is made by using the catalyst and dripped onto a carbon cloth to obtain a battery cathode material; The preparation method of the catalyst consists of the following steps: Step 1: Mix zinc salt, iron salt and organic ligand and add them to a solvent to prepare Fe-ZIF-8 seed crystals; Mix zinc salt, nickel salt and organic ligand and add them to a solvent to prepare Ni-ZIF-8 seed crystals; Step 2: mixing the Fe-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution A; mixing the Ni-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution B; Step 3: Spinning solution A and spinning solution B are placed in two spinning needle tubes respectively, and electrospinning is performed using spinning needles arranged in parallel to obtain nanofibers containing FeNi bimetallic; Step 4: pre-oxidizing the FeNi bimetallic nanofibers prepared in step 3, calcining at 950-1000° C., and then cooling naturally to obtain the catalyst; In step 1, the zinc salt is zinc nitrate hexahydrate; the iron salt is iron nitrate nonahydrate; the nickel salt is nickel nitrate hexahydrate; the mass ratio of the zinc salt, the iron salt and the organic ligand is 28-35:1:33-40; the mass ratio of the zinc salt, the nickel salt and the organic ligand is 2-3:2:9-11; the organic ligand includes dimethylimidazole; and the solvent includes methanol; In step 2, the polymer is polyacrylonitrile and polyvinyl pyrrolidone, and the spinning solvent is N, N-dimethylformamide; the mass ratio of the Fe-ZIF-8 seed crystal, the polymer, and the spinning solvent is 5-7:3:35-40; the mass ratio of the Ni-ZIF-8 seed crystal, the polymer, and the spinning solvent is 5-7:3:35-40; The electrospinning parameters are as follows: applied voltage is 18-22 kV, spinning rate is 1-1.2 mL / h, and receiving distance is 12-15 cm.
2. The preparation method according to claim 1, characterized in that: The preparation method of the catalyst slurry comprises: mixing a catalyst, ethanol and a Nafion solution to obtain the catalyst slurry.
3. The preparation method according to claim 2, characterized in that: In step 4, the pre-oxidation heating rate is 1~2 ℃ / min, air atmosphere, and the pre-oxidation time is 2~3 h; the high-temperature calcination heating rate is 5~6 ℃ / min, nitrogen atmosphere, and the calcination time is 2~3 h.
4. The battery cathode material prepared by the method for preparing the battery cathode material according to claim 1.
5. Application of the battery cathode material prepared by the method for preparing the battery cathode material according to claim 1 in a rechargeable zinc-air battery.
Citation Information
Patent Citations
Method for constructing photoelectricity double function two-stranded parallel nanometer fiber bundle
CN102943317A
Composite air electrode and preparation method thereof
CN115911419A